New Vectors and Strategies for Cardiovascular Gene Therapy - Jazwa, Agnieszka; Jozkowicz, Alicja; Dulak, Jozef (Current Gene Therapy, 2007)
Cardiovascular diseases are the major cause of morbidity and mortality in both men and women in industrially developed countries. These disorders may result from impaired angiogenesis, particularly in response to hypoxia. Despite many limitations, gene therapy is still emerging as a potential alternative for patients who are not candidates for traditional revascularization procedures, like angioplasty or vein grafts. This review focuses on recent approaches in the development of new gene delivery vectors, with great respect to newly discovered AAV serotypes and their modified forms. Moreover, some new cardiovascular gene therapy strategies have been highlighted, such as combination of different angiogenic growth factors or simultaneous application of genes and progenitor cells in order to obtain stable and functional blood vessels in ischemic tissue.
Keywords: endothelial progenitor cells